Konseling dan Batatamba: Belajar dari Budaya Terapeutik Masyarakat Banjar - Rudi Haryadi; Farial Farial (Biblio Couns : Jurnal Kajian Konseling dan Pendidikan, 2022)
Counseling is a process of providing assistance that is not cultureless, bias can occur if a counseling model is applied to various counselees. The Banjar community as a representation of Eastern culture in this case is less familiar with the non-directive and collaborative counseling model. This study aims to examine the therapeutic culture of Batatamba as a local wisdom of the Banjar people, and extract it to build a theoretical basis for Banjar culture sensitive counseling. The research method used is a literature review. Ten key articles were obtained for review after going through the process of selecting keywords, titles, abstracts, and content. The results of the study examine 3 main elements obtained from the Batatamba culture and need to be strengthened by counselors to work with the Banjar community, namely: (1) the charisma/authority of the therapist/counselor as a positive self-quality, (2) public trust in the therapist/counselor, and ( 3) a directive cultural belief-based intervention. Based on the results of this study, further research is recommended to develop a counseling model that is relevant to the cultural characteristics of the Banjar people referring to the 3 elements that have been learned from the Batatamba culture.